2011
DOI: 10.1007/s10549-011-1896-1
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-1 in combination with HER2 and TOP2A for prediction of benefit from adjuvant anthracyclines in high-risk breast cancer patients

Abstract: HER2 amplification, TOP2A aberrations, and absence of tissue inhibitor of metalloproteinase (TIMP-1) expression in breast carcinomas have been shown to be associated with incremental benefit from anthracycline-containing adjuvant chemotherapy, and this study was undertaken to validate these findings in a similar, but independent, randomized clinical trial. TIMP-1 was examined by immunohistochemistry in archival tumor tissue from 403 of 716 premenopausal high-risk patients with known HER2 and TOP2A status who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…Although there are no approaches in clinical use to address this aspect, this is an area that has received much attention. The association between TOP2A or TIMP-1 amplification with response to anthracyclines is one such avenue that has been pursued (45,46). In addition, the stimulation of ErbB3-mediated survival signaling in response to doxorubicin has been observed in some ovarian cancer cell lines (47).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no approaches in clinical use to address this aspect, this is an area that has received much attention. The association between TOP2A or TIMP-1 amplification with response to anthracyclines is one such avenue that has been pursued (45,46). In addition, the stimulation of ErbB3-mediated survival signaling in response to doxorubicin has been observed in some ovarian cancer cell lines (47).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that the 2T profile is a more accurate predictor of incremental benefit from anthracycline-containing chemotherapy than HER2/neu, TIMP-1, or TOP2a individually. 13,63 On contrary, others could not confirm any additive predictive value by combining TIMP-1 immunoreactivity with TOP2a analysis. 52 …”
Section: Discussionmentioning
confidence: 94%
“…The majority of breast cancer studies on TIMP-1 and association with prognosis and response to chemotherapy have focused on patients receiving adjuvant chemotherapy [2,8,18,20,34], whereas only two studies have included patients with advanced breast cancer [35,36]. These two studies both measured TIMP-1 levels in the primary tumors using an enzyme-linked immunosorbent assay-based approach and included patients receiving cyclophosphamide/methotrexate/5-fluorouracil or anthracycline-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…K5007, Dako A/S). TIMP-1 was assessed semi quantitatively using the positive (any cytoplasmatic staining of tumor cells, > 0%) versus negative (no staining of tumor cells) staining signal as a measure of the TIMP-1 immunoreactivity in the epithelial breast cancer cells [2,8,20]. The whole-tissue sections were scanned and examined by light microscopy and reviewed blinded, without knowledge of patient characteristics and outcome, by three independent investigators (pathologist EB and two trained observers, technician AB and biologist CLTJ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation